ORGANIZATIONAL AND LEGAL BASIS OF NATIONAL CULTURAL CENTERS IN THE REPUBLIC OF KARAKALPAKSTAN - Seytimbetova Nargiza Minsizbayevna; Mamutova Guljamal Yeriabil qizi; Kenesbaeva Miyrimpatsha Baxadır qızı (Western European Studies, 2025)
Today, in the era of globalization, when geopolitical and ideological processes are intensifying, as well as in the context of increasing economic, political, national, religious, and other contradictions in the world, ensuring interethnic harmony is one of the main directions of the policy of every state. One of the urgent problems of historical science is the large-scale reforms being carried out in the Republic of Uzbekistan, including in the Republic of Karakalpakstan, in the sphere of interethnic relations, the scientific study of the activities of national cultural centers.
Keywords: language; nation; ethnic identity